THE NECESSITY OF THE RATIONAL CONCEPT FORMATION OF MARKET BEHAVIOR IN MODERN MARKET CONDITIONS - Radionova, N. V. (Science and Transport Progress, 2009)
In the article the tendencies of progress of the consumers’ choice models are considered and the necessity of forming the modern conception of rational marketing is proved.